La produzione linguistica del razzismo ovvero la costruzione di frontiere nell’interazione sociale - Spreafico, Andrea (SocietàMutamentoPolitica, 2019)
This article aims at describing the production of “races” as the result of categorization processes. During the social interactions of everyday life, in its different spheres, borders are linguistically and continuously realised and, in that way, value-related assumptions and moral pre-conceptions – on which discriminatory behaviours of different intensity are sometimes based – are imported. To examine the mechanisms of linguistic production of the border is exactly what will allow us to point out the need of knowing how to maintain ourselves able to abandon our categories, to think the “between” and to perform the crossing.